2019
DOI: 10.1080/15374416.2019.1689824
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Base Update for Brief, Free, and Accessible Youth Mental Health Measures

Abstract: Evidence-based assessment (EBA) is foundational to high-quality mental health care for youth and is a critical component of evidence-based practice delivery, yet is underused in the community. Administration time and measure cost are barriers to use; thus, identifying and disseminating brief, free, and accessible measures are critical. This Evidence Base Update evaluates the empirical literature for brief, free, and accessible measures with psychometric support to inform research and practice with youth. A sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 138 publications
0
42
0
Order By: Relevance
“…Furthermore, many participants commented on the onerous nature of the BASC. Shorter screening measures (e.g., the Patient-Reported Outcomes Measurement Information System-anxiety scale; Pilkonis et al, 2011) would likely be more feasible for teachers (Becker-Haimes et al, 2019). User-centered design strategies also may be helpful for creating/adapting EBIs to fit school contexts (Lyon & Koerner, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many participants commented on the onerous nature of the BASC. Shorter screening measures (e.g., the Patient-Reported Outcomes Measurement Information System-anxiety scale; Pilkonis et al, 2011) would likely be more feasible for teachers (Becker-Haimes et al, 2019). User-centered design strategies also may be helpful for creating/adapting EBIs to fit school contexts (Lyon & Koerner, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We will review clearinghouses of measurement instruments [35] for any additional scales that were missed by the included reviews, and will also make a note of any additional instruments identified while screening for eligibility.…”
Section: Search Strategymentioning
confidence: 99%
“…Several reviews provide overviews of available instruments [28][29][30][31][32][33][34], their measurement properties and feasibility characteristics, but these have tended to be domain-specific (e.g., focusing only on HRQoL); consequently, a comprehensive overview of life impact measures is lacking. On the other hand, broader reviews of mental health assessment tools [e.g., [35][36][37] have not typically been exhaustive in their coverage of life impact measures, and have not tended to examine methodological questions specific to life impact assessment.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] A compendium of these measures is beyond the scope of this pediatrician-friendly analysis, but a comprehensive review is available elsewhere. [29][30][31][32] Consequently, the present work focuses on the PSC-17, PHQ-9, and SCARED for several reasons. First, all three measures are reviewed and recommended in previous large scale authoritative scholarly articles.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of behavioral health screeners available for use with children and adolescents. [29][30][31] A compendium of these measures is beyond the scope of this pediatrician-friendly analysis, but a comprehensive review is available elsewhere. [29][30][31][32] Consequently, the present work focuses on the PSC-17, PHQ-9, and SCARED for several reasons.…”
Section: Introductionmentioning
confidence: 99%